Case Series: Small Full-thickness Macular Hole Treated with Topical Dorzolamide and Bevacizumab Intravitreal Injections. Issue 12 (December 2021) - Feria Anzaldo, Estephania; El Hamichi, Sophia; Gold, Aaron; Latiff, Azeema; Berrocal, Audina M.; Murray, Timothy
Abstract : SIGNIFICANCE: This article reports two cases reported of combined treatment with topical dorzolamide and intravitreal bevacizumab injections, successfully treating small full-thickness macular hole without the need for traditional macular hole surgery. PURPOSE: This study aimed to report the potential effectiveness of combination treatment with topical dorzolamide and bevacizumab intravitreal injection therapy for small macular holes. CASE REPORTS: Case 1 was a 68-year-old woman presented with distorted and decreased vision in her right eye for 9 months. Fundus examination showed a full-thickness macular hole, which was confirmed with spectral domain optical coherence tomography measuring 96 μm. Treatment with topical dorzolamide and intravitreal bevacizumab 1.25 mg/0.05 mL injections was initiated. Spectral domain optical coherence tomography showed gradual improvement of the full-thickness macular hole with complete hole closure and visual improvement in just 1 month. Case 2 was a 73-year-old woman who presented with distorted and decreased vision in her right eye for 8 months. Fundus examination showed a full-thickness macular hole in the right eye, confirmed with spectral domain optical coherence tomography, measuring 76 μm. Treatment with topical dorzolamide and intravitreal bevacizumab 1.25 mg/0.05 mL injections was initiated. Spectral domain optical coherence tomography showed gradual improvement of the full-thickness macular hole with complete closure at 2 months and improvement in visual acuity. CONCLUSIONS: The combination of topical dorzolamide and bevacizumab intravitreal injection is a reasonable consideration for small macular holes with vascular components before considering surgery. Both cases had early macular closure in less than 3 months.